2020
DOI: 10.1097/01.naj.0000662804.81454.66
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Exploring the Effects of a Nurse-Initiated Diary Intervention on Post–Critical Care Posttraumatic Stress Disorder

Abstract: Background: Critical illness survivors may develop posttraumatic stress disorder (PTSD) following critical illness and hospitalization. Left untreated, PTSD may result in poor health outcomes. Purpose: This study sought to examine the effects of a nurse-initiated diary intervention on PTSD development and symptom severity in critical illness survivors with varying levels of mentation. Methods: The study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In addition to randomized controlled studies, we also included two good quality case-control studies in this meta-analysis (Garrouste-Orgeas et al, 2012;Glimelius et al, 2018). These studies also discussed the influence of diaries on symptoms related to PTSD of ICU survivors, with the comparison of case-control clinical outcomes and the results are consistent with a similar recent study (Torres et al, 2020). An earlier study (Garrouste-Orgeas et al, 2012) explored the influence of ICU diaries on the psychological status of critically ill patients and their families at 3 and 12 months after discharge and the results showed that ICU diary significantly reduced the symptoms related to posttraumatic stress of relatives and ICU survivors within 1 year after hospital discharge.…”
Section: Clinical Challenges On Implementing Diary Psychotherapy Of Discharged Icu Patientssupporting
confidence: 83%
“…In addition to randomized controlled studies, we also included two good quality case-control studies in this meta-analysis (Garrouste-Orgeas et al, 2012;Glimelius et al, 2018). These studies also discussed the influence of diaries on symptoms related to PTSD of ICU survivors, with the comparison of case-control clinical outcomes and the results are consistent with a similar recent study (Torres et al, 2020). An earlier study (Garrouste-Orgeas et al, 2012) explored the influence of ICU diaries on the psychological status of critically ill patients and their families at 3 and 12 months after discharge and the results showed that ICU diary significantly reduced the symptoms related to posttraumatic stress of relatives and ICU survivors within 1 year after hospital discharge.…”
Section: Clinical Challenges On Implementing Diary Psychotherapy Of Discharged Icu Patientssupporting
confidence: 83%
“…The first matrix (Fig. 2) included seven trials evaluating the effect of an ICU diary on patients' mental health (7,8,16,(18)(19)(20)(21). In five trials (7,8,16,18,19), the diary was initiated for the group of patients who benefited the most according to healthcare provider perception: patients under mechanical ventilation (MV) for at least 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…All the effective interventions presented three components that patients reported as helpful: they were written by ICU staff, delivered after hospital discharge, and were read with a healthcare provider with whom the patient could ask questions and talk about the ICU stay. As for the two trials in which the sample consisted of patients spontaneously breathing or mechanically ventilated for less than 3 days, one was positive (20), and the other was negative (21). In the positive trial, family members and patients participated in the diary writing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The nurse-initiated diary intervention was found to be effective in decreasing PTSD symptoms among nurses working on hospital inpatient units. 25 Other studies suggest resilience and mindfulness as ways to mitigate the effects of PTSD. 26…”
Section: Discussionmentioning
confidence: 99%